The perceptions of families on receiving forensic mental healthcare users for leave of absence and discharge in Limpopo Province - Rudzani Octovia Bakali; Emmerentia du Plessis; Kathleen Froneman (Elsevier, 2023)
Background: Long stay in forensic mental healthcare hospitals is a risk for forensic mental healthcare users. Families are reluctant to receive such mental healthcare users for leave of absence and discharge. Aim: To explore and describe the perceptions of families on receiving forensic mental health care users for leave of absence and discharge. Methodology: The research used a descriptive qualitative design. The sample size was 13 families, comprising 21 participants. Data was collected through the Mmogo method and interviews. A six-step data analysis strategy was employed. Findings: The families' perceptions were ambivalent, influenced by the behaviour of the forensic mental healthcare user and the type of offense committed. Families accept the forensic mental healthcare user, but endured behavioural, social, psychological, and emotional discomfort. Conclusions: Families' perceptions provide the multidisciplinary team with an understanding of support required by the family prior to re-integrating the forensic mental healthcare user within communities.